Ancient DNA analysis identifies marine mollusc shells as new metagenomic archives of the past. (12th May 2017) - Der Sarkissian, Clio; Pichereau, Vianney; Dupont, Catherine; Ilsøe, Peter C.; Perrigault, Mickael; Butler, Paul; Chauvaud, Laurent; Eiríksson, Jón; Scourse, James; Paillard, Christine; Orlando, Ludovic
Abstract: Marine mollusc shells enclose a wealth of information on coastal organisms and their environment. Their life history traits as well as (palaeo‐) environmental conditions, including temperature, food availability, salinity and pollution, can be traced through the analysis of their shell (micro‐) structure and biogeochemical composition. Adding to this list, the DNA entrapped in shell carbonate biominerals potentially offers a novel and complementary proxy both for reconstructing palaeoenvironments and tracking mollusc evolutionary trajectories. Here, we assess this potential by applying DNA extraction, high‐throughput shotgun DNA sequencing and metagenomic analyses to marine mollusc shells spanning the last 7, 000 years. We report successful DNA extraction from shells, including a variety of ancient specimens, and find that DNA recovery is highly dependent on their biomineral structure, carbonate layer preservation and disease state. We demonstrate positive taxonomic identification of mollusc species using a combination of mitochondrial DNA genomes, barcodes, genome‐scale data and metagenomic approaches. We also find shell biominerals to contain a diversity of microbial DNA from the marine environment. Finally, we reconstruct genomic sequences of organisms closely related to the Vibrio tapetis bacteria from Manila clam shells previously diagnosed with Brown Ring Disease. Our results reveal marine mollusc shells as novel genetic archives of the past, which opens new perspectives in ancient DNA research, with the potential to reconstruct the evolutionary history of molluscs, microbial communities and pathogens in the face of environmental changes. Other future applications include conservation of endangered mollusc species and aquaculture management.